INTEGRASI AGAMA DAN BUDAYA SEBAGAI MEDIA UNTUK MENGUATKAN KEARIFAN LOKAL - Jamal Ma’mur (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2013)
Corruption, collusion, nepotism, globalism, westernism, and secularism have relentlessly bombarded this nation all the times. Therefore, it requires smart, effective, and visionary solutions. So far, this nation has overly lauded globalization by considering the West as the central advancement while the values ​​of wisdom are mostly neglected as it was considered to be old-fashioned. However, the reality shows the contrary perceptions and beliefs. Globalism is an eminent threat that continues to spread poverty, injustice, authoritarianism, dictatorship, and permissive thought on a global scale. It is like a hungry lion that continue to pounce on prey with a strong hegemony and dominance. In this context, the nation is actually longing for ancestral values ​​that had long been neglected. Rational thinking, practices, philosophy, and the track record of the ancestors turned out to contain all-powerful pearls that can drive progress and achieve victory through a more humanistic approach. Such religion and culture are ultimately the most valuable heritage of the ancestors that popularly known as the local wisdom. But unfortunately they often clash each other and it occurs even in a prolonged conflict. So, Islam is challenged to provide solution to this issue. This paper will explore the integration of Islam and local culture as a bridge to reach the local wisdom that is expected to be able in resolving the acute problem of this nation.